A novel method for the synthesis of 2-imidazolones - AlNashef, I.M.; Hashim, M.A.; Mjalli, F.S.; Ali, M.Q.Al-haj.; Hayyan, M. (Elsevier, 2010)
The superoxide ion electrochemically generated by reduction of oxygen, or chemically generated by dissolving potassium superoxide in ionic liquids, reacts with alkyl imidazolium cations of imidazolium-based ionic liquids at room temperature and atmospheric pressure to give the corresponding 2-imidazolones in excellent yields. (C) 2010 Elsevier Ltd. All rights reserved.